Genetic Polymorphisms Involved in Mitochondrial Metabolism and Pancreatic Cancer Risk - Peduzzi, Giulia; Gentiluomo, Manuel; Tavano, Francesca; Arcidiacono, Paolo Giorgio; Ermini, Stefano; Vodicka, Pavel; Boggi, Ugo; Cavestro, Giulia Martina; Capurso, Gabriele; Morelli, Luca; Milanetto, Anna Caterina; Pezzilli, Raffaele; et al. (Cancer epidemiology, biomarkers & prevention, 2021)
BACKGROUND: The mitochondrial metabolism has been associated with pancreatic ductal adenocarcinoma (PDAC) risk. Recent evidence also suggests the involvement of the genetic variability of the mitochondrial function in several traits involved in PDAC etiology. However, a systematic investigation of the genetic variability of mitochondrial genome (mtSNP) and of all the nuclear genes involved in its functioning (n-mtSNPs) has never been reported. METHODS: We conducted a two-phase association study of mtSNPs and n-mtSNPs to assess their effect on PDAC risk. We analyzed 35,297 n-mtSNPs and 101 mtSNPs in up to 55,870 individuals (12,884 PDAC cases and 42,986 controls). In addition, we also conducted a gene-based analysis on 1,588 genes involved in mitochondrial metabolism using Multi-marker Analysis of GenoMic Annotation (MAGMA) software. RESULTS: In the discovery phase, we identified 49 n-mtSNPs and no mtSNPs associated with PDAC risk (P < 0.05). In the second phase, none of the findings were replicated. In the gene-level analysis, we observed that three genes (TERT, SUGCT, and SURF1) involved in the mitochondrial metabolism showed an association below the Bonferroni-corrected threshold of statistical significance (P = 0.05/1588 = 3.1 × 10-5). CONCLUSIONS: Even though the mitochondrial metabolism might be involved in PDAC etiology, our results, obtained in a study with one of the largest sample sizes to date, show that neither n-mtSNPs nor mtSNPs are associated with PDAC risk. IMPACT: This large case-control study does not support a role of the genetic variability of the mitochondrial function in PDAC risk.
Keywords: lidé; Pancreatic Neoplasms; genetická variace; jednonukleotidový polymorfismus; Humans; Mitochondria; genom mitochondriální; nádory slinivky břišní; Genome, Mitochondrial; Polymorphism, Single Nucleotide; Carcinoma, Pancreatic Ductal; Genetic Variation; studie případů a kontrol; mitochondrie; Case-Control Studies; duktální karcinom slinivky břišní